Experiencing Rhythm in Dance - Wilson, John M.; Henley, Matthew (Frontiers in Psychology, 2022)
In this article, two dance educators offer a definition of rhythm from both educational and performance perspectives and discuss pedagogical practices that waken students’ awareness to rhythm as a lived-experience over which they have creative control. For the dancer, in the midst of the dance, rhythms are, in the words of Margaret H’Doubler, recurring patterns of measured energy. These patterns are nested in scales from the moment-to-moment shifts in muscular contraction and release to the rise and fall of dramatic tension in a performed dance. This approach to rhythm runs counter to many dance students’ studio-based training in which rhythm is equated to synchronizing accents to a specific meter. The authors describe pedagogical practices in the studio that foster engagement with rhythm as lived-experience. Drawing attention to their kinesthetic experience while moving, students are encouraged to modulate levels of exertion embedded in the qualities of movement they are experiencing. As varying levels of exertion are attended to across temporal durations, students notice patterns as they emerge and recur. This attention to recurring patterns of measured exertion is, the authors claim, the lived-experience of rhythm in dance.